Evaluation of association between psychological stress and serum cortisol levels in patients with chronic periodontitis - Estimation of relationship between psychological stress and periodontal status - Roshni Jaiswal; Nina Shenoy; Biju Thomas (Wolters Kluwer Medknow Publications, 2016)
Background: Stress classically describes a destructive notion that can have a bearing on one's physical and mental health. It may also add to an increased propensity to periodontal disease. Aim: To investigate the association between psychological stress and serum cortisol levels in patients with chronic periodontitis. Materials and Methods: Forty subjects were recruited from the outpatient department at the Department of Periodontics, from a college in Mangalore, divided into two groups, i.e., twenty as healthy controls and twenty were stressed subjects with chronic periodontitis. The clinical examination included the assessment of probing pocket depth, clinical attachment level and oral hygiene index-simplified. Serum cortisol levels were estimated biochemically using the enzyme-linked immunosorbent assay method and the estimation of psychological stress was done by a questionnaire. Results: Descriptive statistics such as mean and standard deviation was used to review the collected data. Independent sample t-test was used for comparison and correlation was evaluation using Pearson's correlation test. As per our observation, high serum cortisol levels and psychological stress are positively linked with chronic periodontitis establishing a risk profile showing a significant correlation (P < 0.05). Conclusion: Routine serum cortisol assessment may be a reasonable and a valuable investigative indicator to rule out stress in periodontitis patients as it should be considered as an imperative risk factor for periodontal disease.